Technology transfer into LDCs - Rolf Sutter (Intereconomics, 1974)
Multinational enterprises play an important role in the transfer of technology into LDCs. The following article examines the various aspects of the transfer of technology and the attitude of multinational enterprises towards such transfers.
Keywords: 330; Multinational Corporations